Walking George : the Life of George John Beto and the Rise of the Modern Texas Prison System. - Horton, David M. (North Texas Crime and Criminal Justice, 5., 2005)
George John Beto (1916-1991) is best known for his contributions to criminal justice. This book, authored by two of his former students, examines the entire life of Beto and his many achievements in the fields of both education and criminal justice.